2018
DOI: 10.1111/1759-7714.12828
|View full text |Cite
|
Sign up to set email alerts
|

Significance of spread through air spaces in early‐stage lung adenocarcinomas undergoing limited resection

Abstract: BackgroundIn early‐stage lung adenocarcinomas, spread through air spaces (STAS) are reported to be a prognostic factor in patients who have undergone sublobar resection, but not lobectomy. In contrast, reports have also shown that STAS is significantly associated with poor survival outcomes after lobectomy, but not after limited resection. Thus, the prognostic impact of STAS differs according to published reports.MethodsA total of 82 patients with early‐stage adenocarcinomas who underwent limited resection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…In keeping with previous studies, STAS was diagnosed in more than one third of all cases in our series [2,7,12,13,19]. The phenomenon was first described by Onozato and coworkers [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In keeping with previous studies, STAS was diagnosed in more than one third of all cases in our series [2,7,12,13,19]. The phenomenon was first described by Onozato and coworkers [20].…”
Section: Discussionsupporting
confidence: 91%
“…Despite the development of molecular targeted therapies and immune checkpoint inhibitors for the treatment of pulmonary adenocarcinoma, its outcome is still unfavorable [1]. Lobar resection with lymph node dissection remains the most common curative therapy in stage I disease [2,3]. There are several studies in progress aiming to validate the utility of lung sparing or sublobar resection for early stage lung adenocarcinoma and to answer whether lung sparing resection for this disease is only a function preserving or a curative treatment option as well [4].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] However, other studies have not found a survival difference between limited resections and lobectomies. 15,22,24,25 Additionally, the significance of STAS at the resection margin remains to be seen: whereas Masai et al showed that the presence of STAS at the surgical margin may portend a higher local recurrence rate, another study by Eguchi et al reported that the margin/tumour ratio has no impact on the already increased risk of locoregional recurrence. 23,26 The discrepancy in these findings has profound implications for frozen section interpretation of STAS, as its effect on the consideration for lobectomy has real-time consequences intraoperatively.…”
Section: Ongoing Issues Of Discussionmentioning
confidence: 99%
“…Recent studies have proposed the inclusion of a number of additional pathologic features, such as secondary histologic patterns, 20 nuclear grade, [21][22][23] mitotic grade, [22][23][24] presence of spread through airspaces (STAS), [25][26][27][28][29] and necrosis, 30,31 to the predominant pattern classification in an attempt to improve the grading scheme. All these additional histologic features have been reported to have a prognostic value; however, most studies evaluated these features as a single parameter and did not take into account the heterogeneity of pulmonary adenocarcinomas.…”
Section: Introductionmentioning
confidence: 99%